Nursing Care for Disorders of the Integumental System: Debridement of Cellulitis e.c. Diabetes Mellitus Type II a/r Dextra of the Femur and Fibula - Farhan, Zahara; Permana, Gin Gin Sugih (Nursing Case Insight Journal, 2024)
Inflammation of the subcutaneous tissue resulting from Streptococcus aureus and Streptococcus pyogenes bacteria is known as cellulitis. This research study aims to provide practical experience in assessment, diagnosis, planning, execution, and evaluation of direct and comprehensive nursing care for clients with integumentary system issues. When writing in a case study format, descriptive writing is used. These cases had difficulties with restricted physical mobility, poor skin tissue integrity, acute pain, and dietary inadequacies. The study's tactics are tailored to the specific health concerns of each participant, taking into account the predetermined goals and objectives. Addressing the root causes of the issues with the integumentary system is the goal of nursing care. Mr. S showed improvement in the nursing care process evaluation, with three nursing problems fully treated and one partially fixed. The findings of this scientific study align with previously developed tactics. This is inextricably linked to the family's provision of support, guidance from clinical instructors and academic supervisors, and the entire nursing care implementation process for Mr. S, who has integumentary system difficulties